A new Chinese Cyclogethes pollen beetle, with an updated key to species of the genus and notes on its phylogenetic positioning (Coleoptera: Nitidulidae: Meligethinae) - Liu, Meike; Wang, Xinyue; Yang, Xingke; Huang, Min; Audisio, Paolo; Gardini, Pietro; Sabatelli, Simone (Zootaxa, 2024)
A peculiar new species of the genus Cyclogethes Kirejtshuk, 1979, C. tibialis sp. nov., is described from Southwestern China (Yunnan). The new species appears to be morphologically rather isolated from the other known members of this essentially Oriental genus (including half a dozen species from Northern Indian subcontinent, Northern Indochina, and Southwestern China). However, it could be more closely related to C. abnormis Kirejtshuk, 1979 from Northern India, Indochina, and Southwestern China, and to C. aldridgei Kirejtshuk, 1980 from Northern India and Nepal, from which it is easily distinguished by the more elongate body shape, and by the markedly sinuate hind tibiae in both sexes (a very unusual character state in Meligethinae, where only males of some species exhibit sexual secondary characters in the tibial shape). The new species also differs from other known taxa of the genus by the shape of the male and female genitalia. The larval hostplants of members of Cyclogethes are thus far unknown, although some clues, also involving the new species described herein, may suggest a relationship with small trees or shrubs of the family Asteraceae. Preliminary and incomplete molecular data on a studied member of the genus (C. abnormis) seems to not disagree with a phylogenetic positioning of Cyclogethes in a clade including the African genera Tarchonanthogethes Audisio & Cline, 2009, its allied Afrotropical taxa, and the Palaearctic genera Meligethes Stephens, 1830 and Brassicogethes Audisio & Cline, 2009. The article includes an updated identification key for all six known species of this genus and an updated map of their known geographic distribution.